2023
DOI: 10.1186/s13023-023-02695-5
|View full text |Cite
|
Sign up to set email alerts
|

Participation in a national diagnostic research study: assessing the patient experience

Abstract: Introduction The Undiagnosed Diseases Network (UDN), a clinical research study funded by the National Institutes of Health, aims to provide answers for patients with undiagnosed conditions and generate knowledge about underlying disease mechanisms. UDN evaluations involve collaboration between clinicians and researchers and go beyond what is possible in clinical settings. While medical and research outcomes of UDN evaluations have been explored, this is the first formal assessment of the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…All four groups found the UDN process, particularly the comprehensive evaluation, to be beneficial. The majority of groups expressed that participation was a positive experience (Rosenfeld et al, 2023). Additionally, analysis of semi-structured interviews with parents of children evaluated by the UDN found that the diagnostic journey of these patients was complicated by the needs of the parent and the child, especially when they are misaligned and when the child reaches adolescence (Miller et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…All four groups found the UDN process, particularly the comprehensive evaluation, to be beneficial. The majority of groups expressed that participation was a positive experience (Rosenfeld et al, 2023). Additionally, analysis of semi-structured interviews with parents of children evaluated by the UDN found that the diagnostic journey of these patients was complicated by the needs of the parent and the child, especially when they are misaligned and when the child reaches adolescence (Miller et al, 2023).…”
Section: Introductionmentioning
confidence: 99%